2020
DOI: 10.1002/pds.5028
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic inequality in non‐steroidal anti‐inflammatory drug‐associated harm in New Zealand: A national population‐based cohort study

Abstract: PurposeNon‐steroidal anti‐inflammatory drugs (NSAIDs) are associated with many serious complications and they are widely used in New Zealand (NZ). However, differences in NSAID‐associated risk for these complications between ethnic groups are largely unknown. We assessed ethnic disparities in risk of hospital admission for upper gastrointestinal bleeding (UGIB), heart failure, and acute kidney failure (AKF) in NZ's primary care population prescribed and dispensed NSAIDs.MethodsRetrospective cohort study utilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…22 Widespread access to NSAIDs has led to ethnic disparities in hospital admissions of Māori and Pacific peoples for serious adverse outcomesincluding upper gastrointestinal bleeding, heart failure, and acute kidney failure. 23 Māori and Pasifika are less often the recipients of medicines optimisation and are paying the price.…”
Section: Gout and Nsaidsmentioning
confidence: 99%
“…22 Widespread access to NSAIDs has led to ethnic disparities in hospital admissions of Māori and Pacific peoples for serious adverse outcomesincluding upper gastrointestinal bleeding, heart failure, and acute kidney failure. 23 Māori and Pasifika are less often the recipients of medicines optimisation and are paying the price.…”
Section: Gout and Nsaidsmentioning
confidence: 99%
“…In Aotearoa New Zealand (NZ), inequities in health-related outcomes exist, driven by inequities in the access to determinants of health including quality healthcare. 3 Māori are the Indigenous people of NZ and experience earlier onset of chronic co-morbidity, 3 are prescribed higher numbers of medicines from a younger age, 4 experience higher rates of medicine-related harm, 5 and are less likely to be able to access medicines when disease burden is taken into account compared with non-Māori. 6 Access to appropriate medicine therapy for Māori is likely to improve health outcomes and support the achievement of health equity for Māori.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, Māori and Pasifika are more likely to be prescribed NSAIDs than other ethnic groups and have higher rates of associated ADEs and at younger age. 9,10 Trials of interventions to decrease high-risk prescribing in general practice have demonstrated improvements although the quality of evidence is mixed with many studies having short-term follow-up or interventions that are not readily scalable. [11][12][13][14][15][16] One cluster-randomised stepped-wedge trial of a pharmacist-led intervention plus financial incentives found decreased highrisk prescribing of and related ADE hospital admissions, but this trial did not have a true control group.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, Māori, and Pasifika people are more likely than other ethnic groups to be prescribed NSAIDs, and suffer associated ADEs at higher rates and younger ages. 9 , 10…”
Section: Introductionmentioning
confidence: 99%